2008
DOI: 10.1111/j.1467-6494.2008.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Identity Motives Underlying Desired and Feared Possible Future Selves

Abstract: Desired and feared possible future selves are important motivators of behavior and provide a temporal context for self-evaluation. Yet little research has examined why people desire some possible selves and fear others. In two studies, we tested the reflection of identity motives for self-esteem, efficacy, meaning, continuity, belonging, and distinctiveness in people's desired and feared possible future selves and in their possible future identity structures. As predicted, participants desired especially those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
81
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 45 publications
2
81
0
1
Order By: Relevance
“…Goals are more specific and contextualized than possible selves (Oyserman and Markus 1990), and possible selves may be motivating even if they are unattainable Nurius 1986, Markus et al 1990). Importantly, possible selves play a key role in intentional change (Boyatzis and Akrivou 2006, Dunkel 2000, Ibarra 1999, Vignoles et al 2008) and self-development (Lord and Brown 2004), and possible selves offer opportunities to create identities that deviate from current reality Kunda 1986, Markus andNurius 1986).…”
Section: The Role Of Follower Possible Selves In Vision Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Goals are more specific and contextualized than possible selves (Oyserman and Markus 1990), and possible selves may be motivating even if they are unattainable Nurius 1986, Markus et al 1990). Importantly, possible selves play a key role in intentional change (Boyatzis and Akrivou 2006, Dunkel 2000, Ibarra 1999, Vignoles et al 2008) and self-development (Lord and Brown 2004), and possible selves offer opportunities to create identities that deviate from current reality Kunda 1986, Markus andNurius 1986).…”
Section: The Role Of Follower Possible Selves In Vision Communicationmentioning
confidence: 99%
“…Also, as the collective possible self is associated with a positively evaluated collective, the follower will regard it as more desirable (cf. Vignoles et al 2008). …”
Section: Values and Intermediate Goals Scholars Have Argued That Vismentioning
confidence: 99%
“…For example, if a woman perceives herself as ''emotional,'' and fears that she may become even more emotional after becoming mother, this identity element can be said to assume a central position in her feared possible future identity structure. Vignoles et al (2008) have shown that people can report their desires and fears about how existing content will be restructured following assimilation of a new identity element, and that desires and fears about identity restructuring reflect core identity motives as do desired and feared possible future selves. Clearly, this raises interesting questions about the role of these possible future identity structures in the identity accommodation process.…”
mentioning
confidence: 96%
“…For example, if a woman's identity before the transition to parenthood includes the role of ''daughter,'' this identity element could gain or lose importance relative to other elements in her subjective identity structure, after she becomes a mother. Extending this concept of subjective identity structure, we developed the concept of possible future identity structures (see also Vignoles, Manzi, Regalia, Jemmolo, & Scabini, 2008), referring to the importance an individual gives to each of his/her current identity elements in his/her expected, desired, and feared future selves. For example, if a woman perceives herself as ''emotional,'' and fears that she may become even more emotional after becoming mother, this identity element can be said to assume a central position in her feared possible future identity structure.…”
mentioning
confidence: 99%
“…As we have discussed, individuals form a variety of identities, in part in order to satisfy one or more motives [23], but not all identities are relevant in all situations, and people tend to cater their identity communication depending on the context or audience [50]. Thus, following the logic in the preceding paragraphs, identities that are perceived as relevant in a given situation will be most likely to be communicated.…”
Section: H2: Identities That Satisfy An Individual's (A) Selfverificamentioning
confidence: 99%